A water-resistant RCO catalyst and preparation method thereof

By forming a metal organic frame material on the surface of the titanium-cerium composite oxide microspheres of the RCO catalyst and filling it with 12-crown-4-ether, anchoring the platinum group metal, a water-resistant RCO catalyst is prepared, which solves the problem of pore blockage in the existing catalysts when treating brine vapor, and achieves higher processing efficiency and service life.

CN119259119BActive Publication Date: 2025-04-04HANGZHOU HUISHUI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411782867.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-04
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

When existing RCO catalysts treat flue gas containing brine vapor, the pores are prone to clogging, resulting in low processing efficiency and short service life.

Method used

Using titanium-cerium composite oxide microspheres as cores, water-resistant RCO catalysts were prepared by growing metal organic frame materials in situ on their surface and filling the pores with 12-crown-4-ether.

Benefits of technology

The catalyst's tolerance to the flue gas containing brine vapor is improved, the pore blockage is avoided, the service life of the catalyst is extended, and the treatment efficiency of volatile organic matter is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a water-resistant RCO catalyst and a preparation method thereof, the preparation method of the water-resistant RCO catalyst comprising the following steps: taking tetrabutyl titanate, cerium nitrate, methyl laurate polyoxyethylene ether, acetic acid, ethanol, mixing evenly, after heat treatment, drying, roasting, and obtaining titanium-cerium composite oxide microspheres; taking titanium-cerium composite oxide microspheres, adding cerium nitrate, organic ligand, N, N-dimethylformamide, 12-crown-4-ether thereto, mixing evenly, and after reaction, obtaining core-shell structure particles; adding platinum group metal precursors to the core-shell structure particles, after reaction, obtaining a water-resistant RCO catalyst. The catalyst obtained by the present invention has a good treatment effect for volatile organic compounds in flue gas, good tolerance for salt water vapor, is not prone to problems such as blocking catalyst pores after crystallization of salt water vapor, and can maintain a high treatment efficiency for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, in particular to a water-resistant RCO catalyst and a preparation method thereof. Background Art

[0002] A large amount of flue gas is emitted during industrial production, and the composition of the flue gas is complex, including various pollutants such as particulate matter, sulfur oxides, nitrogen oxides, heavy metals, and organic pollutants. Volatile organic compounds (VOCs) in flue gas can usually be treated after bag dust removal, alkaline washing spray desulfurization, and activated carbon dehumidification. The treatment can be carried out using RCO (Regenerative Catalytic Oxidizer) technology, which uses a catalyst to oxidize and decompose combustible substances in the flue gas at a lower temperature, thereby achieving flue gas purification.

[0003] In the catalytic combustion treatment process of volatile organic matter in flue gas, although the flue gas is dehumidified by activated carbon, there is still a lot of water vapor, and the water vapor contains a certain amount of salt, and its conductivity can reach 3000~6000us / cm. When the salty water vapor in the flue gas crystallizes on the surface of the RCO catalyst, it is easy to block the pores of the catalyst, reduce the flux and treatment efficiency, and shorten the service life of the catalyst. Summary of the invention

[0004] The object of the present invention is to provide a water-resistant RCO catalyst to solve the problems of low treatment efficiency of RCO catalysts in the prior art for flue gas containing salt water vapor and easy clogging of pores.

[0005] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0006] A method for preparing a water-resistant RCO catalyst comprises the following steps:

[0007] (1) Tetrabutyl titanate, cerium nitrate, methyl laurate polyoxyethylene ether, acetic acid and ethanol are mixed evenly, and after heat treatment, they are dried and calcined to obtain titanium-cerium composite oxide microspheres;

[0008] (2) taking the titanium-cerium composite oxide microspheres obtained in step (1), adding cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, mixing them evenly, and reacting to obtain core-shell structured particles;

[0009] The core-shell structure particles have titanium-cerium composite oxide microspheres as cores, the surface of which is covered with a metal organic framework material, and the pores of the metal organic framework material are filled with the 12-crown-4-ether;

[0010] (3) Adding a platinum group metal precursor to the core-shell structured particles obtained in step (2), and after reaction, the platinum group metal is anchored on the 12-crown-4-ether to obtain a water-resistant RCO catalyst.

[0011] Preferably, step (1) specifically includes: mixing tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol evenly, adding an aqueous solution of cerium nitrate thereto, mixing evenly, heat treating in an autoclave at 160-180°C for 12-24h, drying at 90-100°C for 2-5h, heating to 460-520°C at a rate of 5-10°C / min, and calcining for 1-3h to obtain titanium-cerium composite oxide microspheres.

[0012] Preferably, in step (1), the molar ratio of tetrabutyl titanate to cerium nitrate is 1:(0.1-0.6);

[0013] The mass ratio of the tetrabutyl titanate, the methyl laurate polyoxyethylene ether and the acetic acid is 1:(0.05-0.15):(1-3);

[0014] The volume ratio of the tetrabutyl titanate to the anhydrous ethanol is 1:(0.8-1.2);

[0015] In the aqueous solution of cerium nitrate, the mass fraction of cerium nitrate is 2-5wt%.

[0016] Preferably, in step (2), the organic ligand is one of 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid and 2,5-bis(trifluoromethyl)terephthalic acid.

[0017] Preferably, step (2) specifically includes: taking the titanium-cerium composite oxide microspheres obtained in step (1), adding cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, stirring at 20-40°C for 2-10 hours, and then reacting at 80-120°C for 10-20 hours, centrifuging and separating the solid product, and drying to obtain core-shell structured particles.

[0018] Preferably, in step (2), the mass ratio of cerium nitrate, organic ligand and 12-crown-4-ether is 1:(1.2-1.8):(0.1-0.3);

[0019] The volume ratio of the N,N-dimethylformamide to the cerium nitrate is 1:(100-300).

[0020] Preferably, step (3) specifically comprises: dissolving a platinum group metal precursor in a solvent to obtain a platinum group metal precursor solution; adding the platinum group metal precursor solution to the core-shell structured particles obtained in step (2), stirring for 4-12 hours, centrifuging and separating the solid product, washing and drying it, placing it in a hydrogen atmosphere, and performing a reduction reaction at 140-160° C. for 1-3 hours to obtain a water-resistant RCO catalyst.

[0021] Preferably, in step (3), the platinum group metal precursor is one of the precursors of platinum, palladium and rhodium; wherein the platinum precursor includes platinum acetylacetonate and platinum chloride; the palladium precursor includes palladium acetylacetonate and palladium chloride; and the rhodium precursor includes rhodium acetylacetonate and rhodium chloride.

[0022] The solvent is one of methanol, ethanol, water and N,N-dimethylformamide.

[0023] Preferably, in step (3), the concentration of the platinum group metal precursor in the platinum group metal precursor solution is 2-4 mg / ml;

[0024] The mass ratio of the core-shell structure particles to the platinum group metal precursor is 1:(0.01-0.06).

[0025] It should be noted that the CAS number of the 2,5-bis(trifluoromethyl)terephthalic acid is 89803-71-4; the CAS number of the 2,5-bis(trifluoromethyl)terephthalic acid is 366008-67-5. The CAS number of the 12-crown-4-ether is 294-93-9.

[0026] The present invention also provides a water-resistant RCO catalyst, which is obtained by the preparation method of the water-resistant RCO catalyst.

[0027] Preferably, the water-resistant RCO catalyst has the titanium-cerium composite oxide microspheres as the core and the metal-organic framework material as the shell, the 12-crown-4-ether is filled in the nanopores of the metal-organic framework material, and the platinum group metal is anchored on the 12-crown-4-ether.

[0028] The above solution of the present invention includes at least the following beneficial effects:

[0029] (1) The preparation method of the water-resistant RCO catalyst of the present invention comprises the following steps: taking tetrabutyl titanate, cerium nitrate, methyl laurate polyoxyethylene ether, acetic acid, and ethanol, mixing them evenly, and drying and calcining them after heat treatment to obtain titanium-cerium composite oxide microspheres; taking the obtained titanium-cerium composite oxide microspheres, adding cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, mixing evenly, and reacting to obtain core-shell structure particles; the core-shell structure particles have titanium-cerium composite oxide microspheres as cores, and the surface is covered with metal organic framework materials, and the pores of the metal organic framework materials are filled with the 12-crown-4-ether; adding a platinum group metal precursor to the core-shell structure particles, and after the reaction, the platinum group metal is anchored on the 12-crown-4-ether to obtain a water-resistant RCO catalyst. In the above process, the tetrabutyl titanate and cerium nitrate use the methyl laurate polyoxyethylene ether as a template to synthesize titanium-cerium composite oxide microspheres. Then, the titanium-cerium composite oxide microspheres are used as cores, and a shell material is grown in situ on the surface thereof; in the shell material, cerium nitrate and organic ligands form a metal organic framework material, and the 12-crown-4-ether is loaded in the pore structure of the metal organic framework material. Finally, a platinum group metal precursor is added thereto, and under the action of the coordinating oxygen atoms of the 12-crown-4-ether, the platinum group metal is anchored on the 12-crown-4-ether.

[0030] The water-resistant RCO catalyst of the present invention has a good treatment effect on volatile organic compounds in flue gas, especially when treating flue gas containing salt water vapor, it has good tolerance to salt water vapor, is not prone to problems such as clogging catalyst pores after crystallization of salt water vapor, and can maintain a high treatment efficiency for a longer period of time. The details are as follows:

[0031] First, the titanium-cerium composite oxide microspheres have good thermal stability and chemical stability, good salt resistance, and can provide stable support for the metal organic framework material of the outer layer, so that the catalyst maintains a complete structure and achieves a longer service life. Second, there is a synergistic catalytic effect between the titanium-cerium composite oxide microspheres and the metal organic framework material anchored with platinum group metals. The platinum group metals have high catalytic activity, and the cerium oxide in the titanium-cerium composite oxide microspheres can provide oxygen vacancies and have certain redox properties. It can form a charge compensation effect on the surface of the catalyst shell through charge transfer, reduce the influence of water vapor on the catalyst, thereby improving the catalyst's tolerance to water vapor and preventing excessive accumulation and crystallization of salts on the catalyst surface. The two materials of the core-shell cooperate with each other to jointly promote the transfer of electrons and the adsorption-desorption process of reactants, so that the oxidation reaction of organic matter can be carried out at a lower temperature, reduce the activation energy of the reaction, and improve the rate and efficiency of the catalytic reaction.

[0032] In addition, the titanium-cerium composite oxide microspheres are synthesized using methyl laurate polyoxyethylene ether as a template, and the methyl laurate polyoxyethylene ether can form micelles in the solution to prevent the aggregation and precipitation of the microspheres, and as a nonionic surfactant, it will not produce strong electrostatic interference to the ions in the reaction system, which is conducive to the full formation of a solid solution between cerium and titanium, and the formation of a solid solution will disturb the lattice of titanium, causing lattice defects of titanium, causing changes in oxygen mobility, and then as an active site, providing a nucleation site for cerium nitrate and an organic ligand to form the metal organic framework material, guiding the metal organic framework material to grow uniformly on the surface of the microspheres, and forming a strong interface bond. This not only helps to form a stable core-shell structure, but also facilitates charge transfer between the core-shell structures.

[0033] The metal organic framework material has a large specific surface area and rich pore structure, and the cyclic flexible structure of the 12-crown-4-ether can adjust its shape to a certain extent to adapt to the pore structure, and then be firmly wrapped in the pore of the metal organic framework material. The 12-crown-4-ether ring contains multiple ether oxygen atoms, which can provide lone pairs of electrons to form coordination bonds with single atoms of the platinum group metal to restrict their movement, thereby effectively preventing the aggregation of single atoms of the platinum group metal, and making the single atoms of the platinum group metal uniformly distributed on the metal organic framework material to achieve excellent catalytic activity.

[0034] (2) In the water-resistant RCO catalyst of the present invention, the organic ligand is one of 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid and 2,5-bis(trifluoromethyl)terephthalic acid. The organic ligand contains a trifluoromethyl group, which can reduce the surface energy of the catalyst and effectively enhance the hydrophobicity of the catalyst. Due to the repulsive effect of the trifluoromethyl group on water molecules, water vapor is not easily adsorbed and condensed on the surface, thereby reducing the deposition of salt near the pores and making it difficult to form stable crystal nuclei on the catalyst surface, thereby inhibiting the crystallization process.

[0035] In particular, when the organic ligand is 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid, the biphenyl structure provides a larger non-polar region for the molecule, and the two trifluoromethyl groups are located at both ends of the biphenyl structure, so that the hydrophobicity of the entire molecule is further enhanced, and the crystalline salt formed by the salty water vapor is difficult to adhere firmly to the surface of the catalyst and is easy to fall off, thereby reducing the phenomenon of pore blockage. DETAILED DESCRIPTION

[0036] In the embodiments of the present invention, if the specific conditions are not specified, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Raw materials of different manufacturers and models do not affect the implementation of the technical solution of the present invention and the realization of the technical effects.

[0037] In the following examples, the methyl laurate polyoxyethylene ether used is a product in the prior art, for example, it can be prepared by the method disclosed in Chinese patent document CN109627431B.

[0038] Example 1

[0039] The preparation method of the water-resistant RCO catalyst of this embodiment comprises the following steps:

[0040] (1) Tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol were mixed evenly, and then an aqueous solution of cerium nitrate was added thereto. After mixing evenly, the mixture was heat treated in an autoclave at 160°C for 12 h, dried at 100°C for 3 h, heated to 490°C at a rate of 5°C / min, and calcined for 1 h to obtain titanium-cerium composite oxide microspheres.

[0041] Among them, the molar ratio of the tetrabutyl titanate and cerium nitrate is 1:0.1; the mass ratio of the tetrabutyl titanate, the methyl laurate polyoxyethylene ether and the acetic acid is 1:0.10:1; the volume ratio of the tetrabutyl titanate and the anhydrous ethanol is 1:1.0; in the aqueous solution of cerium nitrate, the mass fraction of cerium nitrate is 2wt%.

[0042] (2) Take the titanium-cerium composite oxide microspheres obtained in step (1), add cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, stir at 30°C for 2 hours, react at 80°C for 15 hours, separate the solid product by centrifugation, and dry to obtain core-shell structured particles. The core-shell structured particles have titanium-cerium composite oxide microspheres as cores, the surface of which is covered with a metal organic framework material, and the pores of the metal organic framework material are filled with the 12-crown-4-ether.

[0043] The organic ligand is 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid. The mass ratio of the cerium nitrate, the organic ligand, and 12-crown-4-ether is 1:1.2:0.2; and the volume ratio of the N,N-dimethylformamide to the cerium nitrate is 1:100.

[0044] (3) dissolving a platinum group metal precursor in a solvent to obtain a platinum group metal precursor solution; adding the platinum group metal precursor solution to the core-shell structured particles obtained in step (2), stirring for 8 hours, separating the solid product by centrifugation, washing and drying, placing the solid product in a hydrogen atmosphere, and performing a reduction reaction at 140° C. for 2 hours to anchor the platinum group metal to the 12-crown-4-ether, thereby obtaining a water-resistant RCO catalyst.

[0045] The platinum group metal precursor is a platinum precursor, specifically platinum acetylacetonate; the solvent is methanol; the concentration of the platinum group metal precursor in the platinum group metal precursor solution is 3 mg / ml; and the mass ratio of the core-shell structure particles to the platinum group metal precursor is 1:0.01.

[0046] The water-resistant RCO catalyst obtained in this embodiment has the titanium-cerium composite oxide microspheres as the core and the metal organic framework material as the shell. The 12-crown-4-ether is filled in the nanopores of the metal organic framework material, and the platinum group metal is anchored on the 12-crown-4-ether.

[0047] Example 2

[0048] The preparation method of the water-resistant RCO catalyst of this embodiment comprises the following steps:

[0049] (1) Tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol were mixed evenly, and then an aqueous solution of cerium nitrate was added thereto. After mixing evenly, the mixture was heat treated in an autoclave at 180°C for 18 h, dried at 95°C for 2 h, heated to 520°C at a rate of 10°C / min, and calcined for 3 h to obtain titanium-cerium composite oxide microspheres.

[0050] Among them, the molar ratio of the tetrabutyl titanate and the cerium nitrate is 1:0.6; the mass ratio of the tetrabutyl titanate, the methyl laurate polyoxyethylene ether and the acetic acid is 1:0.15:2; the volume ratio of the tetrabutyl titanate and the anhydrous ethanol is 1:1.2; in the aqueous solution of cerium nitrate, the mass fraction of cerium nitrate is 5wt%.

[0051] (2) Take the titanium-cerium composite oxide microspheres obtained in step (1), add cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, stir at 40°C for 10 hours, react at 100°C for 20 hours, separate the solid product by centrifugation, and dry to obtain core-shell structured particles. The core-shell structured particles have titanium-cerium composite oxide microspheres as cores, the surface of which is covered with a metal organic framework material, and the pores of the metal organic framework material are filled with the 12-crown-4-ether.

[0052] The organic ligand is 2,5-bis(trifluoromethyl)terephthalic acid. The mass ratio of the cerium nitrate, the organic ligand, and 12-crown-4-ether is 1:1.8:0.3; and the volume ratio of the N,N-dimethylformamide to the cerium nitrate is 1:300.

[0053] (3) dissolving a platinum group metal precursor in a solvent to obtain a platinum group metal precursor solution; adding the platinum group metal precursor solution to the core-shell structured particles obtained in step (2), stirring for 4 hours, separating the solid product by centrifugation, washing and drying, placing the solid product in a hydrogen atmosphere, and performing a reduction reaction at 160° C. for 3 hours, so that the platinum group metal is anchored on the 12-crown-4-ether, thereby obtaining a water-resistant RCO catalyst.

[0054] The platinum group metal precursor is a palladium precursor, specifically palladium chloride; the solvent is ethanol; the concentration of the platinum group metal precursor in the platinum group metal precursor solution is 4 mg / ml; the mass ratio of the core-shell structure particles to the platinum group metal precursor is 1:0.06.

[0055] The water-resistant RCO catalyst obtained in this embodiment has the titanium-cerium composite oxide microspheres as the core and the metal organic framework material as the shell. The 12-crown-4-ether is filled in the pores of the metal organic framework material, and the platinum group metal is anchored on the 12-crown-4-ether.

[0056] Example 3

[0057] The preparation method of the water-resistant RCO catalyst of this embodiment comprises the following steps:

[0058] (1) Tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol were mixed evenly, and then an aqueous solution of cerium nitrate was added thereto. After mixing evenly, the mixture was heat treated in an autoclave at 170°C for 24 hours, dried at 90°C for 5 hours, heated to 460°C at a rate of 8°C / min, and calcined for 2 hours to obtain titanium-cerium composite oxide microspheres.

[0059] Among them, the molar ratio of the tetrabutyl titanate and the cerium nitrate is 1:0.3; the mass ratio of the tetrabutyl titanate, the methyl laurate polyoxyethylene ether and the acetic acid is 1:0.05:3; the volume ratio of the tetrabutyl titanate and the anhydrous ethanol is 1:0.8; in the aqueous solution of cerium nitrate, the mass fraction of cerium nitrate is 3wt%.

[0060] (2) Take the titanium-cerium composite oxide microspheres obtained in step (1), add cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, stir at 20°C for 6 hours, react at 120°C for 10 hours, separate the solid product by centrifugation, and dry to obtain core-shell structured particles. The core-shell structured particles have titanium-cerium composite oxide microspheres as cores, the surface of which is covered with a metal organic framework material, and the pores of the metal organic framework material are filled with the 12-crown-4-ether.

[0061] The organic ligand is 2,5-bis(trifluoromethyl)terephthalic acid. The mass ratio of the cerium nitrate, the organic ligand, and 12-crown-4-ether is 1:1.5:0.1; and the volume ratio of the N,N-dimethylformamide to the cerium nitrate is 1:200.

[0062] (3) dissolving a platinum group metal precursor in a solvent to obtain a platinum group metal precursor solution; adding the platinum group metal precursor solution to the core-shell structured particles obtained in step (2), stirring for 12 hours, separating the solid product by centrifugation, washing and drying, placing the solid product under a hydrogen atmosphere, and performing a reduction reaction at 150° C. for 1 hour to anchor the platinum group metal to the 12-crown-4-ether, thereby obtaining a water-resistant RCO catalyst.

[0063] The platinum group metal precursor is a rhodium precursor, specifically rhodium acetylacetonate; the solvent is water; in the platinum group metal precursor solution, the concentration of the platinum group metal precursor is 2 mg / ml; and the mass ratio of the core-shell structure particles to the platinum group metal precursor is 1:0.03.

[0064] The water-resistant RCO catalyst obtained in this embodiment has the titanium-cerium composite oxide microspheres as the core and the metal organic framework material as the shell. The 12-crown-4-ether is filled in the nanopores of the metal organic framework material, and the platinum group metal is anchored on the 12-crown-4-ether.

[0065] Example 4

[0066] The preparation method of the water-resistant RCO catalyst of this embodiment comprises the following steps:

[0067] (1) Tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol are mixed evenly, and then an aqueous solution of cerium nitrate is added thereto. After mixing evenly, the mixture is heat treated in an autoclave at 170°C for 15 h, dried at 100°C for 5 h, heated to 500°C at a rate of 8°C / min, and calcined for 3 h to obtain titanium-cerium composite oxide microspheres.

[0068] Among them, the molar ratio of the tetrabutyl titanate and cerium nitrate is 1:0.4; the mass ratio of the tetrabutyl titanate, the methyl laurate polyoxyethylene ether and the acetic acid is 1:0.8:2; the volume ratio of the tetrabutyl titanate and the anhydrous ethanol is 1:1.2; in the aqueous solution of cerium nitrate, the mass fraction of cerium nitrate is 4wt%.

[0069] (2) Take the titanium-cerium composite oxide microspheres obtained in step (1), add cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, stir at 30°C for 10 hours, react at 120°C for 18 hours, separate the solid product by centrifugation, and dry to obtain core-shell structured particles. The core-shell structured particles have titanium-cerium composite oxide microspheres as cores, the surface of which is covered with a metal organic framework material, and the pores of the metal organic framework material are filled with the 12-crown-4-ether.

[0070] The organic ligand is 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid. The mass ratio of cerium nitrate, organic ligand and 12-crown-4-ether is 1:1.6:0.2; and the volume ratio of N,N-dimethylformamide to cerium nitrate is 1:300.

[0071] (3) dissolving a platinum group metal precursor in a solvent to obtain a platinum group metal precursor solution; adding the platinum group metal precursor solution to the core-shell structured particles obtained in step (2), stirring for 8 hours, separating the solid product by centrifugation, washing and drying, placing the solid product in a hydrogen atmosphere, and performing a reduction reaction at 150° C. for 3 hours, so that the platinum group metal is anchored on the 12-crown-4-ether, thereby obtaining a water-resistant RCO catalyst.

[0072] The platinum group metal precursor is a platinum precursor, specifically platinum chloride; the solvent is N,N-dimethylformamide; the concentration of the platinum group metal precursor in the platinum group metal precursor solution is 3 mg / ml; and the mass ratio of the core-shell structure particles to the platinum group metal precursor is 1:0.05.

[0073] The water-resistant RCO catalyst obtained in this embodiment has the titanium-cerium composite oxide microspheres as the core and the metal organic framework material as the shell. The 12-crown-4-ether is filled in the nanopores of the metal organic framework material, and the platinum group metal is anchored on the 12-crown-4-ether.

[0074] Comparative Example 1

[0075] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, with the only difference being that in step (1), cerium nitrate is not included, and the obtained product is titanium oxide microspheres.

[0076] In this comparative example, step (1) specifically includes: uniformly mixing tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol, heat treating in an autoclave at 170°C for 15 h, drying at 100°C for 5 h, heating to 500°C at a rate of 8°C / min, and calcining for 3 h to obtain titanium oxide microspheres.

[0077] Comparative Example 2

[0078] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (2), the organic ligand is replaced by 2,5-bis(trifluoromethyl)terephthalic acid from the 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid.

[0079] Comparative Example 3

[0080] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (2), the organic ligand is replaced by terephthalic acid from the 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid.

[0081] Comparative Example 4

[0082] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (1), the methyl laurate polyoxyethylene ether is replaced by nonylphenol polyoxyethylene ether.

[0083] Comparative Example 5

[0084] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (1), the methyl laurate polyoxyethylene ether is replaced by lauryl alcohol polyoxyethylene ether.

[0085] Comparative Example 6

[0086] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (1), the methyl laurate polyoxyethylene ether is replaced by sodium dodecyl sulfate.

[0087] Comparative Example 7

[0088] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, with the only difference being that in step (2), the 12-crown-4-ether is not contained.

[0089] Comparative Example 8

[0090] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (2), the 12-crown-4-ether is replaced by 15-crown-5 ether.

[0091] Wherein, the CAS number of the 15-crown-5 ether is 33100-27-5.

[0092] Comparative Example 9

[0093] The water-resistant RCO catalyst of this comparative example has the same raw materials and the same preparation method as that of Example 4, and the only difference is that in step (2), the 12-crown-4-ether is replaced by 18-crown-6 ether.

[0094] Wherein, the CAS number of the 18-crown-6 ether is 17455-13-9.

[0095] Effect experiment example

[0096] In order to verify the technical effect of the preparation method of the water-resistant RCO catalyst described in the present invention, the following experiments were conducted:

[0097] The water-resistant RCO catalyst was prepared by the method in Examples 1-4 and Comparative Examples 1-9, and its catalytic combustion performance was evaluated. 50 mg of each group of catalysts were taken and loaded into a tubular furnace reactor, and simulated dry coal-fired flue gas, simulated moist coal-fired flue gas, and simulated salt-containing moist coal-fired flue gas were introduced into the reactor respectively. The catalytic reaction was carried out under the conditions of reaction temperature of 350°C, stabilization time of 60min, reaction flow rate of 200mL / min, and volume space velocity of 120000h-1. The reaction tail gas was analyzed online by gas chromatograph to calculate the toluene removal rate, and the toluene removal rate of the catalyst after 24h of continuous catalytic reaction of simulated salt-containing moist coal-fired flue gas was calculated.

[0098] The simulated dry coal-fired flue gas has a toluene concentration of 50 ppm, a SO2 concentration of 1000 ppm, a NO concentration of 500 ppm, and an NH3 concentration of 500 ppm, and contains 5 vol% O2, with N2 as the balance gas.

[0099] The simulated wet coal-fired flue gas has a toluene concentration of 50 ppm, a SO2 concentration of 1000 ppm, a NO concentration of 500 ppm, and an NH3 concentration of 500 ppm, and contains 5 vol% O2, 10 vol% water vapor, and N2 is the balance gas;

[0100] The simulated salt-containing wet coal-fired flue gas has a toluene concentration of 50 ppm, a SO2 concentration of 1000 ppm, a NO concentration of 500 ppm, an NH3 concentration of 500 ppm, an inorganic salt concentration of 50 ppm, and contains 5 vol% O2, 15 vol% water vapor, and N2 is the balance gas.

[0101] After experimentation, the results are as follows:

[0102]

[0103] According to the results of Examples 1-4 and Comparative Examples 1-9, the water-resistant RCO catalyst of the present invention has a good treatment effect on volatile organic matter in flue gas, especially when treating flue gas containing salt water vapor, it has good tolerance to salt water vapor, is not prone to problems such as clogging the catalyst pores after the salt water vapor crystallizes, and can maintain a high treatment efficiency for a longer time.

[0104] According to the results of Example 4 and Comparative Example 1, the toluene removal rate of dry coal-fired flue gas, the toluene removal rate of wet coal-fired flue gas, and the toluene removal rate of salt-containing wet coal-fired flue gas using the titanium-cerium composite oxide microspheres are all high, and after continuous catalysis of salt-containing wet coal-fired flue gas, the toluene removal rate of the catalyst only slightly decreases. It can be seen that compared with titanium oxide microspheres, the titanium-cerium composite oxide microspheres can not only improve the catalyst's treatment efficiency for volatile organic compounds, but also improve the catalyst's tolerance to water vapor and reduce the transitional accumulation and crystallization of salts on the catalyst surface.

[0105] According to the results of Example 4 and Comparative Examples 4-6, the use of different surfactants has a certain influence on the obtained titanium-cerium composite oxide microspheres, and further affects the comprehensive performance of the catalyst. Among them, the effect of non-ionic surfactants is better than that of ionic surfactants, and the effect of methyl laurate polyoxyethylene ether is better than that of other non-ionic surfactants.

[0106] According to the results of Example 4 and Comparative Examples 2-3, the organic ligand has a significant effect on the treatment efficiency of volatile organic compounds. This is because the difference in the organic ligand will lead to different pore structures of the metal organic framework formed, which will affect the encapsulation of the 12-crown-4-ether, thereby causing the distribution of the catalytically active platinum group metal on the metal organic framework material to change. In addition, the difference in the organic ligand also affects the hydrophobicity of the catalyst. In terms of tolerance to water vapor, it shows that 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid>2,5-bis(trifluoromethyl)terephthalic acid>terephthalic acid.

[0107] According to the results of Example 4 and Comparative Examples 7-9, different crown ethers as stabilizers of the platinum group metals have significantly different catalytic effects on the obtained catalysts, but the difference in water vapor tolerance of the catalysts is relatively small. This may be because the 12-crown-4-ether has the best compatibility with the pore structure of the metal organic framework material, which is more conducive to exposing the active sites on the crown ether to anchor the platinum group metal.

[0108] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are encompassed by the present invention.

Claims

1. A method for preparing a water-resistant RCO catalyst, characterized in that: The steps include: (1) Tetrabutyl titanate, cerium nitrate, methyl laurate polyoxyethylene ether, acetic acid and ethanol are mixed evenly, heat treated in an autoclave at 160-180° C. for 12-24 h, dried and calcined to obtain titanium-cerium composite oxide microspheres; (2) Take the titanium-cerium composite oxide microspheres obtained in step (1), add cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, mix well, and react at 80-120° C. for 10-20 hours to obtain core-shell structured particles; The core-shell structure particles have titanium-cerium composite oxide microspheres as cores, the surface of which is covered with a metal organic framework material, and the pores of the metal organic framework material are filled with the 12-crown-4-ether; the organic ligand is one of 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-dicarboxylic acid and 2,5-bis(trifluoromethyl)terephthalic acid; (3) Adding a platinum group metal precursor to the core-shell structured particles obtained in step (2), placing the particles in a hydrogen atmosphere, and performing a reduction reaction at 140-160° C. for 1-3 h, so that the platinum group metal is anchored on the 12-crown-4-ether, thereby obtaining a water-resistant RCO catalyst.

2. The method for preparing a water-resistant RCO catalyst according to claim 1, characterized in that: The step (1) specifically comprises: uniformly mixing tetrabutyl titanate, methyl laurate polyoxyethylene ether, acetic acid and anhydrous ethanol, adding an aqueous solution of cerium nitrate thereto, uniformly mixing, heat treating in an autoclave at 160-180° C. for 12-24 h, drying at 90-100° C. for 2-5 h, heating to 460-520° C. at a rate of 5-10° C. / min, and calcining for 1-3 h to obtain titanium-cerium composite oxide microspheres.

3. The method for preparing a water-resistant RCO catalyst according to claim 2, characterized in that: In step (1), the molar ratio of tetrabutyl titanate to cerium nitrate is 1:(0.1-0.6); The mass ratio of the tetrabutyl titanate, the methyl laurate polyoxyethylene ether and the acetic acid is 1:(0.05-0.15):(1-3); The volume ratio of the tetrabutyl titanate to the anhydrous ethanol is 1:(0.8-1.2); In the aqueous solution of cerium nitrate, the mass fraction of cerium nitrate is 2-5wt%.

4. The method for preparing a water-resistant RCO catalyst according to claim 3, characterized in that: Step (2) specifically includes: taking the titanium-cerium composite oxide microspheres obtained in step (1), adding cerium nitrate, organic ligand, N,N-dimethylformamide, and 12-crown-4-ether thereto, stirring at 20-40° C. for 2-10 hours, and then reacting at 80-120° C. for 10-20 hours, centrifuging and separating the solid product, and drying to obtain core-shell structure particles.

5. The method for preparing a water-resistant RCO catalyst according to claim 1, characterized in that: Step (3) specifically comprises: dissolving a platinum group metal precursor in a solvent to obtain a platinum group metal precursor solution; adding the platinum group metal precursor solution to the core-shell structure particles obtained in step (2), stirring for 4-12 hours, centrifuging and separating the solid product, washing and drying it, placing it in a hydrogen atmosphere, and performing a reduction reaction at 140-160° C. for 1-3 hours to obtain a water-resistant RCO catalyst.

6. The method for preparing a water-resistant RCO catalyst according to claim 5, characterized in that: In step (3), the platinum group metal precursor is one of platinum, palladium and rhodium precursors; The solvent is one of methanol, ethanol, water and N,N-dimethylformamide.

7. The method for preparing a water-resistant RCO catalyst according to claim 6, characterized in that: In step (3), the concentration of the platinum group metal precursor in the platinum group metal precursor solution is 2-4 mg / ml; The mass ratio of the core-shell structure particles to the platinum group metal precursor is 1:(0.01-0.06).

8. A water-resistant RCO catalyst, characterized in that: The catalyst is obtained by the preparation method of the water-resistant RCO catalyst according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Production method of fatty acid methyl ester polyoxyethylene ether

    CN109627431B

  • Method for catalyzing methanol to achieve dehydrogenation by adopting Pd@CeO2-CNx nuclear shell type catalyst

    CN109622009A

  • Preparation method and application of metal oxide multi-core-silicon-aluminum shell bifunctional catalyst

    CN117138824A